The year in tech, 2024. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2024)
"A year of HBR's essential thinking on tech--all in one place. Generative AI, Web3, neurotech, reusable rockets to power the space economy--new technologies like these are reshaping organizations at the hybrid office, on factory floors, and in the C-suite. What should you and your company be doing now to take advantage of the new opportunities these technologies are creating--and avoid falling victim to disruption? The Year in Tech 2024: The Insights You Need from Harvard Business Review will help you understand what the latest and most important tech innovations mean for your organization and how you can use them to compete and win in today's turbulent business environment. Business is changing. Will you adapt or be left behind?Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues--blockchain, cybersecurity, AI, and more--each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow. You can't afford to ignore how these issues will transform the landscape of business and society. The Insights You Need series will help you grasp these critical ideas--and prepare you and your company for the future."--ProQuest website.
Introduction : integrative technologies are the new business reality / by David De Cremer -- Neurotech at work / by Nita A. Farahany -- Why build in Web3 / by Jad Esber and Scott Duke Kominers -- ChatGPT is a tipping point for AI / by Ethan Mollick -- Leveraging new tech to bring supply chains closer to home / by Suketu Gandhi -- Your company's data is for sale on the dark web : should you buy it back? / by Brenda R. Sharton -- How one airline is using AR to improve operations / by Ting Li, Jason Wang, and Fei Wu -- The metaverse will enhance--not replace--companies' physical locations / by Vladislav Boutenko, Richard Florida, and Julia Jacobson -- Dehumanization is a feature of gig work, not a bug / by Eric M. Anicich -- A platform approach to space exploration / by Atif Ansar and Bent Flyvbjerg -- Does Elon Musk have a strategy? / by Andy Wu and Goran Calic -- AI with a human face / Lingyao (Ivy) Yuan.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed March 7, 2024).
WorldCat record variable field(s) change: 050
Keywords: Business -- Technological innovations; Industrial management; Success in business; Affaires -- Innovations; Gestion d'entreprise.; Succès dans les affaires